Ultraprocessed Food Consumption is Strongly and Dose‐Dependently Associated with Excess Body Weight in Swiss Women. Issue 3 (23rd February 2021) - Pestoni, Giulia; Habib, Linda; Reber, Emilie; Rohrmann, Sabine; Staub, Kaspar; Stanga, Zeno; Faeh, David
Abstract : Objective: This study investigated the association between ultraprocessed food consumption and excess body weight in a Swiss nationally representative study. Methods: Data stem from the cross‐sectional Swiss National Nutrition Survey menuCH ( n  = 2, 057). Dietary information was collected with 24‐hour dietary recalls, and food items were categorized into non‐ultraprocessed or ultraprocessed using the NOVA food classification system. The following three excess body weight indicators were considered: BMI, waist circumference (WC), and a BMI‐WC composite outcome. Multinomial logistic regression models stratified by sex were fitted. Results: Women in the highest quintile of ultraprocessed food weight proportion had significantly higher odds of having obesity (odds ratio [OR] 3.01, 95% CI: 1.48‐6.11), having abdominal obesity (OR 2.69, 95% CI: 1.43‐5.05), and being in the highest category of the BMI‐WC composite outcome (OR 3.28, 95% CI: 1.59‐6.77). No relevant associations were observed in men. Conclusions: Ultraprocessed food weight proportion was strongly and dose‐dependently associated with excess body weight in women but not in men. Further studies are required to elucidate potential mechanisms behind this association. Increasing evidence of the detrimental effect of ultraprocessed food consumption on health stresses the need to consider these products in future public health strategies.